A multilevel study of position effects in PISA achievement tests: student- and school-level predictors in the German tracked school system. Issue 4 (4th July 2019) - Nagy, Gabriel; Nagengast, Benjamin; Frey, Andreas; Becker, Michael; Rose, Norman
Abstract: Position effects (PE) cause decreasing probabilities of correct item responses towards the end of a test. We analysed PEs in science, mathematics and reading tests administered in the German extension to the PISA 2006 study with respect to their variability at the student- and school-level. PEs were strongest in reading and weakest in mathematics. Variability in PEs was found at both levels of analysis. PEs were stronger for male students, for students with a migration background (science and mathematics), and for students with a less favourable socio-economic background (reading). At the school level, PEs were stronger in lower school tracks and in schools with a high proportion of students with a migration background. The relationships of the test scores with the covariates partly reflected the covariates' relationships with PEs. Our findings suggest that PEs should be taken seriously in large-scale assessments as they have an undesirable impact on the results.